Loss Estimation for Network-Connected UAV/RPAS Communications - Svitlana I. Ilnytska; Fengping Li; Andrii Grekhov; Vasyl Kondratiuk (IEEE Access, 2020)
The recent applications of Unmanned Aerial Vehicles (UAVs) and Remotely Piloted Air Systems (RPAS) often require reliable and fast two-way communications between UAVs, base stations and consumers using terrestrial cellular networks. Two crucial questions are whether existing ground networks can effectively interact with UAVs in three-dimensional space during intensive traffic and under what data transmission modes it is possible to provide the necessary Quality of Service (QoS). To answer this question, the UAV/RPAS communication channel model “BS-ATM-HUB-RPAS” with a ground network was designed and investigated. The dependencies of dropped packets, message Travel Time (TT) and HUB Average Utilization on the Transaction Size (TS), the link bandwidth, the Bit Error Rate (BER) and the Packet Fail Chance for different distribution laws of Time Between Transactions (TBT) were analyzed. A significant benefit has been observed in using the LogNormal TBT distribution law rather than the Const and Exponential TBT distributions for the dependencies of dropped packets versus TS, HUB Average Utilization versus TS, and HUB Average Utilization versus link bandwidth. However, for the dependency of message Travel Time on the Transaction Size, the type of TBT distribution did not play a significant role; for all distributions, with increasing transaction size, the time of their transmission via the channel was increased. The importance and usefulness of such a numerical analysis lies in the ability to set traffic parameters and observe the resulting throughput, packet loss, and number of bit errors and QoS in a channel under certain transmission modes.